Merlin Expression in Spiral Ganglion Neurons Is Decreased in Deafened Mice. (23rd August 2013) - Tokita, Joshua; Fernando, Augusta; Harpole, Bethany; Shah, Hetel; Hansen, Marlan R.
Abstract : Objectives: 1) Evaluate the expression and phosphorylation status of merlin, the protein product of the Nf2 tumor suppressor gene, in auditory neural structures before and after deafening. 2) Determine the extent to which merlin influences neurite growth in spiral ganglion neurons (SGNs). 3) Determine whether merlin expression in SGNs or spiral ganglion Schwann cells (SGSCs) inhibits neurite growth. Methods: Immunostaining of cochlear sections before and after deafening and organotypic explants with anti‐merlin antibodies were used to assess merlin expression in SGNs and SGSCs. A (Tx)‐inducible Cre‐mediated recombination system was used to knock out merlin in neonatal SGNs. Cultures were maintained with (+) or without (‐) Tx for 24h to induce Cre expression. To evaluate loss of merlin expression in SGNs versus SGSCs, we plated (+)Tx and (‐)Tx neurons onto a bed of (+)Tx and (‐)Tx SGSCs. Neurite length and branching were determined for each condition. Results: Merlin expression in SGNs raises the possibility that merlin regulates SGN neurite growth. Merlin expression in SGNs decreased in cochlear sections taken from P30 versus P60 control rats and in P30 and P60 deafened versus P30 and P60 control rats respectively. Reduced merlin expression in cultured neurons but not SCs significantly increases both the number and length of SGN neurites in SGNs. Conclusions: The pattern of merlin expression and phosphorylation following deafening in SGNs and SGSCs taken together with results indicating that neuronal expression of merlin inhibits neurite growth raises the possibility that merlin plays a role in auditory neural maintenance, regeneration, or both.